Peran Pemerintah Dalam Pengawasan Keselamatan dan Kesehatan Kerja Dinas Tenaga Kerja dan Transmigrasi Provinsi Jawa Timur (K3) Kepada Para Pekerja di Lingkungan Tempat Kerja - Sahranafa, Karima; Kriswibowo, Arimurti (IAI Nasional Laa Roiba Bogor, 2024)
The Supervisor of the East Java Province Manpower and Transmigration service has a role in ensuring occupational safety and health in his area. One of its roles is to facilitate services in the field of work safety, organize monitoring efforts for workers and the community, as well as medical laboratory services and environmental testing laboratories. The aim of this research is to determine the role of the East Java Province Manpower and Transmigration Service in carrying out in-depth occupational safety and health supervision of entrepreneurs/companies in the workplace environment. The research uses a qualitative research method with a descriptive approach. In this research, the data sources used to complete the writing are primary data sources and secondary data sources. So the data analysis in this research is based on 3 (three) Government roles in monitoring occupational safety and health namely Regulator, Dynamisator, Facilitator. The results of the research show that the role ofthe government of the East Java Manpower and Transmigration Service has not been carried out optimally because the government lacks direct attention to see the obstacles experienced by workers, both in terms of guidance and training, as well as facilities and infrastructure which are not distributed evenly